Guardian of the horizon - Peters, Elizabeth (New York : William Morrow, 2004)
Ousted from their most recent archaeological dig and banned forever from the Valley of the Kings, the Emersons are spending a quiet summer at home in Kent, England, when a mysterious messenger arrives. Claiming to be the teenage brother of their dear friend, Tarek, Prince of the mysterious Lost Oasis, the charismatic herald brings troubling news of a strange malady that has struck down Tarek's heir and conveys his brother's urgent need for help only th Emersons can provide. The family sets off in secret for the land time forgot to a mountain fortress from which they narrowly escaped ten years before
Keywords: Peabody, Amelia (Fictitious character); Excavations (Archaeology); Women archaeologists; British; Egyptologists